ELEANOR MITCHELL, PEGGY SEIDEN, and SUZY TARABA, eds., Past or Portal? Enhancing Undergraduate Learning through Special Collections and Archives - Robicheau, Wendy G. (Archivaria, 2013)
Past or Portal? Enhancing Undergraduate Learning through Special Collections and Archives . ELEANOR MITCHELL, PEGGY SEIDEN, and SUZY TARABA, eds. Chicago: Association of College and Research Libraries, 2012. xiii, 320 p. ISBN 978-083898610-3.